Html 4.0 - MacK, E. Stephen; Platt, Janan (Sybex Inc, San Franciso, 1997)
HTML is the fundamental coding language of the Internet and intranets--soon it will be built into the next version of Windows itself! This book is all anyone needs to learn and create commercial-quality Web pages. Focusing on essential practical skills--like using frames, tables, forms, images, Java applets, ActiveX controls, and much more--this book turns novices into real Web programmers faster than any other book of its kind. All the latest versions of HTML are covered, including tags in Netscape Communicator, MS Internet Explorer 4, and the next version of Windows. Readers also get a code that lets them download utilities, examples from the book, and free clip art.